Morphological and physiological properties of kratom (Mitragyna speciosa) leaves: Macronutrients, phytochemicals, antioxidants, and mitragynine content - Phromchan, Wethanee; Defri, Ifwarisan; Saensano, Chutikarn; Chookaew, Anuthida; Chiarawipa, Rawee; Sriwiriyajan, Somchai (Plant Science Today, 2024)
Morpho-physiological characteristics of leaves are significantly associated with photosynthetic capacity and leaf growth. This study was designed to evaluate the relationship between leaf functional traits, nutrients, and their active compounds throughout the developmental stages of kratom leaves. Five growth stages were identified: S1 (7-15 days), S2 (15-30 days), S3 (30-45 days), S4 (45-60 days), and S5 (60-75 days). A comparison of leaf-group stages was conducted based on morpho-physiological traits, macronutrient content, phytochemical analysis, and antioxidant activity. The results revealed that leaf weight and leaf area increased from S1 to S5, with a slight decrease observed in S5. Stomatal density remained similar across all stages. In contrast, chlorophyll and carotenoid contents showed a steady increase up to the S5 stage. The maximum assimilation rate (Amax) and light-saturated photosynthetic rate (Pmax) were achieved at the S2 and S3 stages. Macronutrient levels (N, P, and K) were highest in the younger leaf-group stages (S1 to S2) and significantly different from the older leaf-group stages (S4 to S5). The highest amount of phenolics, flavonoids, and antioxidant activity were found in the middle leaf-group stage (S3). However, anthocyanin content tended to decrease with leaf-group stages. Moreover, the mitragynine content continuously decreased with leaf age, with the highest content found in the young (S1 to S2) and middle (S3) group stages of leaves. Therefore, the productive phytochemical contents in the fully expanded leaves should be considered, especially mitragynine content, which is mainly used in medicinal products.